Hemodynamic Determinants of Age Versus Left Ventricular Diastolic Function Relations Across the Full Adult Age Range. Issue 6 (June 2020) - Bello, Hamza; Norton, Gavin R.; Peterson, Vernice R.; Mmopi, Keneilwe N.; Mthembu, Nonhlanhla; Libhaber, Carlos D.; Masiu, Mohlabani; Da Silva Fernandes, Daniel; Bamaiyi, Adamu J.; Peters, Ferande; Sareli, Pinhas; Woodiwiss, Angela J.
Abstract : The relative contribution of loading conditions at different ages across the full adult lifespan to decreases in left ventricular (LV) diastolic function is unclear. Using central arterial pressure and aortic velocity and diameter measurements in the outflow tract, we determined the contribution of systemic vascular resistance, compression wave pressures (characteristic impedance [Zc]×aortic flow [Q], [PQ×Zc ]) and backward wave pressures (Pb) to LV diastolic function (echocardiography) in a community sample across the full adult lifespan (n=605). Starting from early adulthood, stepwise age-related increases in LV filling pressures (E/e') and decreases in myocardial relaxation (e') were noted ( P <0.0001). Before 50 years of age, before when PQ×Zc positively correlates with age, Pb, but not systemic vascular resistance was independently associated with LV mass index ( P <0.002), E/e' ( P <0.002), and e' ( P <0.05). Moreover, in those over 50 years of age, when PQ×Zc positively correlates with age, again Pb, but neither PQxZc nor systemic vascular resistance was independently associated with LV mass index ( P <0.01), E/e' ( P <0.001), and e' ( P <0.001). The contribution of Pb to age-related decreases in LV diastolic function was as strong in those younger as compared with older than 50 years of age and poorly indexed by brachial BP. In conclusion, a striking age-related deterioration in LV diastolic function begins at an early adult age and Pb is the dominant hemodynamic factor that accounts for this relationship. Age-related increases in Pb in young adults contribute as much to functional abnormalities ultimately responsible for LV diastolic dysfunction in hypertension as at an older age, effects poorly indexed by brachial BP. Abstract : Supplemental Digital Content is available in the text.